(untitled) (Research, Society and Development, 2022)
The objective is to know the therapeutic constructs of COVID-19 in its first year of the pandemic. This is a narrative review of the literature, carried out from research in the Biblioteca Virtual de Saúde, Periódicos Capes, PubMed, Cochrane with the standardized descriptors ’Therapy’ AND COVID-19, in the first year of the COVID-19 pandemic, after the official declaration of the WHO. As a result, the researched therapeutic targets (in vivo, in vitro, in silico) and published in the first year of this health crisis were described. It was evident that the therapies explored were based on pharmacological and non-pharmacological targets on the host, immune system the virus. The main agents tested in vitro, in vivo, in silico belong to the pharmacological classes of antivirals, antiparasitics, anti-inflammatories, antibiotics as well as monoclonal antibodies, stem cells convalescent plasma. According to the publications, the most cited drugs to treat COVID-19 were hydroxychloroquine, chloroquine, ivermectin, azithromycin, vitamin D, dexamethasone glucocorticoid. It was found that many therapeutic strategies against COVID-19 have been refuted, however, others are being better researched.